PEREMPUAN DI DALAM SINETRON: PENCITRAAN MEDIA MASSA TERHADAP PEREMPUAN - Anam, Miftakhul (Yinyang: Jurnal Studi Islam Gender dan Anak, 2009)
Based from values embraced by society, women suffering unequal image compared with men. There’s opinion existed insociety that women was positioned as men’s subordinate, women was complement of existence of a dynasty, and women is weak being.One source of this bias image is from television. Through one popular program named sinetron (TV drama series), women once moreplunged into dark and moron age